Writing the history of South African universities: Trends and themes - Maylam, P. (South African Journal of Higher Education, 2024)
This article examines the historiography of South African universities. In recent years a number of histories of individual universities have been published. The article traces the evolution of such historical works and discusses the different types of such histories that have appeared over the years. The main part of the article focuses on the most significant themes that have been addressed by the authors of these histories.